Variable Stoichiometry and Homeostatic Regulation of Bacterial Biomass Elemental Composition - Scott, Thad; Cotner, James; LaPara, Timothy (Frontiers in Microbiology, 2012)
Heterotrophic bacteria represent a large proportion of global biomass, and therefore bacterial biomass stoichiometry likely exerts control on global phosphorus (P), carbon (C) and nitrogen (N) cycling and primary productivity. In this study we grew recently-isolated freshwater heterotrophic bacteria across an ecologically relevant range of resource C:P ratios (ratio of organic C to available P) to quantify the P requirements of these organisms and examine the degree to which they regulated their P content under P-sufficient and P-deficient conditions. Bacterial biomass was only limited by P when resource C:P was greater than 250 (by atoms). Bacterial C:P ranged from 71 – 174 under P sufficiency and from 252 – 548 under P deficiency. Bacteria exhibited very little C:P homeostasis under P-sufficient growth conditions, greater C:P homeostasis under P-deficient conditions, and the ability of bacteria to outcompete one another in short-term experiments depended on a tradeoff between storing excess P for later use under P deficient conditions or immediately using P to produce more biomass. These results indicate that freshwater heterotrophic bacteria are not as P-rich as previously thought and that homeostatic regulation of C:P stoichiometry depends on the individual taxa and what resource (organic C or available P) is limiting bacterial growth. The prevalence of homeostatic and non-homeostatic strategies and nutrient limitation in a community should have important implications for nutrient regeneration and carbon cycling.